PENGGUNAAN MICROSOFT MATH 4.0 UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Ilmadi _; Yulianti Rusdiana (Universitas Muhammadiyah Semarang, 2019)
This study aims to improve students' understanding of mathematical concepts through the use of Ms Math 4.0 software in the learning process. This research was conducted using a quasi-experimental method with a quantitative approach. There are two sample groups in this study: the experimental group which was carried out using Ms Math 4.0 and the control group with conventional learning. The method used is quasi-experimental using the Mann Whitney U test for data analysis. From the analysis results obtained: 1) Understanding the concept of students who learn by using Ms Math 4.0 software is higher than those who do not use software; 2) Understanding the concept of students with high, medium and low initial ability who learn by using Ms Math 4.0 software is higher than students who study with conventional learning.